Celebrity enactments of addiction on Twitter. (December 2019) - Dwyer, Robyn; Fraser, Suzanne
Commentators suggest the social media platform, Twitter, might afford challenges to hegemonic knowledge by providing voice to those outside traditional media and by enabling vigorous public discussion and contestation of dominant ideas and concepts. In this article, we ask whether such affordances might be reshaping the culturally charged concept of addiction and, in turn, its accompanying abject and maligned subject, the 'addict'. To explore this question, we examine Twitter messages about addiction posted by celebrities. These people are among the most highly followed Twitter account holders, meaning their Twitter messages can reach millions of people. Our analysis examines how specific addiction problems, and their solutions, are being constituted through the tweeting practices of celebrities. We also consider the unintentional effects these messages produce. Finally, we examine the ways in which these messages are discussed and contested by the audiences of the celebrities. We find celebrity Twitter activity re-enacts familiar realities of addiction, realities that collapse drug use with harm and addiction, addiction with pathology and death. Abstinence is posed as the only effective and genuine response, and the contradictions in simultaneously individualizing action against addiction and condemning stigmatization are ignored. Despite the 'revolutionary' potential of Twitter posited by advocates and some scholars, when it comes to addiction, it seems, the global, uncensored, 'free' communication on Twitter serves largely to validate and perpetuate dominant addiction concepts and the stigma and discrimination these concepts evoke.